Diurnal differences in urine flow in healthy young men in a light-controlled environment: a randomized crossover design - Hiromitsu Negoro; Isuzu Nakamoto; Sayaka Uiji; Yoshiko Matsushima; Bryan J. Mathis; Dominika Kanikowska; Tomoko Wakamura (Journal of Physiological Anthropology, 2023)
Abstract Background Older men often experience nocturnal urination difficulties, reflected by diurnal differences in maximum urine flow (Qmax). Since lower urinary tract symptoms and pathological comorbidities are frequent in older men, it remains unclear whether this diurnal variation is a physiological or pathological phenomenon. Our aim was to quantify the diurnal variability of Qmax in healthy young participants under varying daylight conditions in a stable environment to discern potential underlying causes of nocturnal urination difficulties. Methods Twenty-one healthy young men were recruited in a 4-day study utilizing daytime (08:00–18:00) exposure with two light conditions in randomized order: dim (< 50 lx) or bright (~2500 lx). Day 1 was for acclimation, and urine flow was assessed from day 2. The participants urinated ad libitum during day 2 and then at fixed 3–4-h intervals thereafter (days 3–4). Regular urination Qmax at late night (04:00) on day 4 was compared with the nearest voided volume during daytime of day 3 (mDay). Results Morning Qmax scores (after bed—11:00) on day 2 were significantly lower than evening (17:00—before pre-sleep) in bright conditions and those of daytime (11:00–17:00), evening (17:00—before pre-sleep), and pre-sleep in dim conditions. Pre-sleep Qmax during the ad libitum period was significantly higher in dim than bright conditions. Late-night Qmax values (04:00) on day 4 were significantly lower than Qmax scores of mDay on day 3 in both light conditions. Conclusions Healthy young men had a clear diurnal Qmax difference that decreased during late night and morning. In addition, the pre-sleep Qmax values in dim daylight were significantly higher than in bright daylight. Taken together, we conclude that late-night and morning decreases in Qmax are an instinctive physiological phenomenon in humans, and the diurnal difference of Qmax can be influenced by daylight conditions.